Fish diversity, fishing gears and their catch in the upper Matamuhury river of southeastern Bangladesh - Arshad ul Alam, M; Azadi, M A (Journal of Biodiversity Conservation and Bioresource Management, 2024)
Finfish richness, their abundance, fishing gears and their catch in the upper Matamuhuri river were studied from January to December 2022 along the river course at hilly upstream of Bandarban Hill District. A total of 95 freshwater finfish species under 69 genera belonging to 36 families under 14 orders were recorded in this mountainous section of this river. Maximum number of species were recorded under the Family Cyprinidae (19 species) followed by Danionidae (11 species) and Bagridae (7 species). Amongst 95 finfish species 11 belonged to ‘endangered’ and 12 to ‘vulnerable’ category of threatened species and four were data deficient (e.g. Barilius barila, Balitora brucei, Eleotris lutea and Oryzias dancena) according to IUCN conservation status. Neolissochilus sp. and Golden Mahashol (Tor puttitora) are reported for the first time from the upstream of Matamuhuri River. A systematic list of recorded finfish with their English names, local names, abundance and conservation status is presented. Under eight categories, 16 types of fishing gears and their catch were documented of which two types of gears (Large push net - Haddi Jal and Bowl trap - Bati Trap) were new and not reported elsewhere earlier. Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 15-28